The complete chloroplast genome of Butomus umbellatus L. and its phylogenetic position - Yang, Zhaoping (Mitochondrial DNA B Resour, 2019)
Butomus umbellatus, which belongs to Butomaceae, is a plant species typical of littoral communities of river and stream shores. Here, we reported and characterized the complete chloroplast (cp) genome of B. umbellatus and analyzed its phylogenetic position based on the complete cp genome sequences of 10 species within the core Alimatales. The cp genome is 158,107 bp in length, which consists of a large single-copy region (LSC, 88,140 bp； GC content: 34.8%), a small single-copy region (SSC, 19,695 bp; GC content: 30.1%), and a pair of inverted repeat regions (IRs, 25,136 bp; GC content: 42.9%). It harbours 113 unique genes, including 79 protein-coding genes, 30 transfer RNA genes, and 4 ribosomal RNA genes with an overall GC content of 36.8%. The phylogeny inference showed that Butomaceae and Hydrochariaceae formed a high supported clade, which was sister to Alismataceae. This result was similar to the floral development from petaloid Alismatales, and also similar to the phylogenetic studies of Alismales based on 83 plastid genes, but with much higher bootstrap support.